Development of ILeMBA to Improve Class V Student Learning Outcomes in Science and Technology Lesson Content in Tegal Regency Elementary Schools - Aimatul Zaqiyah; Elok Fariha Sari (Studies in Learning and Teaching, 2024)
In learning, to make it easier for students to understand the material, it is necessary to use media. This research aims to develop and test the feasibility, practicality, and effectiveness of ILeMBA in improving student learning outcomes in Natural and Social Sciences (IPAS) material on the structure of the earth's layers in class V elementary school. This type of research is Research & Development (R&D) with the Borg and Gall model which is limited to the eighth stage of this research. The research subjects involved 27 students (14 female students and 13 male students). The instruments used are expert validator sheets, needs questionnaires, responses, and test questions. The validation results from media experts reached 91% and 93% from material experts showed that the media was "very feasible". Teachers and students responded well, with a teacher response score of 100% and an average student score of 95%, entering the "very practical" criteria. The calculated t-test value is greater than the t-table on a small scale of 4.973 > 2.228 and on a large scale of 11.998 > 2.2021. The results of the N-Gain test scores on a small scale of 79% and a large scale of 91%, show a very high significant difference and improvement in student learning outcomes on the pretest and posttest. Thus, it can be concluded that ILeMBA is proven to be able to improve the learning outcomes of class V students in Natural and Social Sciences (IPAS) material on the structure of the earth's layers (natural and artificial features in waters and land).